2015
DOI: 10.1016/j.learninstruc.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Early language and executive skills predict variations in number and arithmetic skills in children at family-risk of dyslexia and typically developing controls

Abstract: Two important foundations for learning are language and executive skills. Data from a longitudinal study tracking the development of 93 children at family-risk of dyslexia and 76 controls was used to investigate the influence of these skills on the development of arithmetic. A two-group longitudinal path model assessed the relationships between language and executive skills at 3–4 years, verbal number skills (counting and number knowledge) and phonological processing skills at 4–5 years, and written arithmetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 75 publications
9
39
0
2
Order By: Relevance
“…Of special interest with respect to the overlap between MD and RD are mathematical subskills, such as arithmetic fluency, that do not only build on number skills but also require language (Geary & Hoard, ). Language skills are the precursors of verbal number skills, such as counting and transcoding (reading and writing numbers), which in turn affect arithmetic skills (LeFevre et al., ; Moll, Snowling, Göbel, & Hulme, ). Evidence that poor language indeed affects mathematical skills comes from studies showing that individuals with poor language or literacy skills perform more poorly in aspects of mathematics that depend upon verbal abilities (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Of special interest with respect to the overlap between MD and RD are mathematical subskills, such as arithmetic fluency, that do not only build on number skills but also require language (Geary & Hoard, ). Language skills are the precursors of verbal number skills, such as counting and transcoding (reading and writing numbers), which in turn affect arithmetic skills (LeFevre et al., ; Moll, Snowling, Göbel, & Hulme, ). Evidence that poor language indeed affects mathematical skills comes from studies showing that individuals with poor language or literacy skills perform more poorly in aspects of mathematics that depend upon verbal abilities (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results found by Moll et al . () who found that phonetic awareness and executive control, associated with active analysis and verbal reasoning precursors, predicted variations in later school performance. Results provide empirical support for a broader set of correlated precursor abilities beyond phonemic awareness that are involved in reading achievement (Castels & Coltheart, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive fitness is expressed in the literature as the state of our ability to carry out cognitive tasks with vigour and alertness, to learn, and to adapt efficiently to all circumstances (Gläscher et al ., , ; Jung & Haier, ; Oberauer, Suß, Wilhelm, & Wittman, ; Salthouse, ; Shelton, Elliott, Matthews, Hill, & Gouvier, ). Cognitive fitness depends on the development of precursor abilities that include verbal reasoning, visual synthesis, and active analysis; these abilities predispose a child to learn uniquely yet characteristically (Brunswich, Matin, & Rippon, ; Moll, Snowling, Göbel, & Hulme, ; Titz & Karbach, ).…”
Section: Introductionmentioning
confidence: 99%
“…Language and phonological processing are also involved in more sophisticated aspects of mathematics. According to the triple code model (Dehaene, 1992), the verbal-phonological code is used when establishing and retrieving arithmetic facts, and research suggests that reading skills and phonological processing contribute to early mathematical development (Hecht, Torgesen, Wagner, & Rashotte, 2001 Moll, Snowling, Göbel, and Hulme (2015), who found that phonological awareness did not predict arithmetic skills when both oral language ability and executive functions were included in their models. Nevertheless, the authors highlight the role of language and executive functions in early arithmetic skills in children.…”
Section: Language Abilitymentioning
confidence: 99%